Food taboo, dietary diversity and prevalence of chronic energy deficiency in pregnant women living in rural area Indonesia - Dudung Angkasa; Dwi Nastiti Iswarawanti; Otte Santika (JKP (Jurnal Keperawatan Padjajaran), 2024)
Background: Chronic energy deficiency is strongly associated with poor pregnancy outcomes. Food taboo and dietary diversity are suspected as main risk factors of chronic energy deficient in pregnant women in rural area. Nevertheless, none studies elaborated the inferential relationship of those factors with chronic energy deficiency during pregnancy.